2017
DOI: 10.5194/acp-17-4627-2017
|View full text |Cite
|
Sign up to set email alerts
|

Annual variation in event-scale precipitation <i>δ</i><sup>2</sup>H at Barrow, AK, reflects vapor source region

Abstract: Abstract. In this study, precipitation isotopic variations at Barrow, AK, USA, are linked to conditions at the moisture source region, along the transport path, and at the precipitation site. Seventy precipitation events between January 2009 and March 2013 were analyzed for δ2H and deuterium excess. For each precipitation event, vapor source regions were identified with the hybrid single-particle Lagrangian integrated trajectory (HYSPLIT) air parcel tracking program in back-cast mode. The results show that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…For each event, GDAS reanalysis data were used to determine the range of altitudes where condensation occurred, and this range was divided into 1,000 air parcels, each representing an equal proportion of condensing water. The method for dividing the parcels and identifying the moisture source is described by Putman, Feng, Sonder et al () and Putman, Feng, Posmentier et al (). All 1,000 parcels were tracked backward in time for 240 hr, and the water vapor source for a given trajectory was taken to be the first location where the back trajectory sank into the planetary boundary layer (as defined by GDAS).…”
Section: Methodsmentioning
confidence: 99%
“…For each event, GDAS reanalysis data were used to determine the range of altitudes where condensation occurred, and this range was divided into 1,000 air parcels, each representing an equal proportion of condensing water. The method for dividing the parcels and identifying the moisture source is described by Putman, Feng, Sonder et al () and Putman, Feng, Posmentier et al (). All 1,000 parcels were tracked backward in time for 240 hr, and the water vapor source for a given trajectory was taken to be the first location where the back trajectory sank into the planetary boundary layer (as defined by GDAS).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, precipitation and ice cores in Alaska sometimes show stronger correlations between water isotope ratios and moisture source region than temperature (Fisher et al, 2004;Putman et al, 2017), and modern precipitation measurements in the tropical Pacific suggest that isotope ratios respond more sensitively to variations in the intensity and organization of convection regionally than to the amount of local precipitation (Conroy et al, 2016;Kurita, 2013;Kurita et al, 2009;Moerman et al, 2013). More recently, studies have shown correlations between isotope ratios and regional imbalances in E and P (Feng et al, 2009;Lee et al, 2007;Moore et al, 2014) or associated variations in atmospheric residence time and moisture transport (Aggarwal et al, 2012;Bailey et al, 2017;Putman et al, 2017). Nevertheless, to decipher changes in hydrologic balance from isotope ratios, a strong theoretical framework that can explain these correlations is necessary.…”
Section: 1029/2018gl078254mentioning
confidence: 99%
“…Furthermore, existing data typically represent isotopic measurements of monthly composited precipitation samples (IAEA/ WMO, 2018), thereby precluding any ability to identify process-based mechanisms that influence individual precipitation events. While some efforts to delineate spatial patterns of δ 18 O P and δ 2 H P have been carried out using measured and/or modeled data (Anderson et al, 2016;Bailey et al, 2015;Berkelhammer et al, 2012;Field et al, 2010;Putman et al, 2017), longterm empirical data from Alaska are severely lacking in comparison to the contiguous United States (Akers et al, 2017;Liu et al, 2010;Vachon et al, 2010aVachon et al, , 2010bWelker, 2000Welker, , 2012.…”
Section: Introductionmentioning
confidence: 99%